The Politics of Knowledge and Theory Construction in Adult Education: A Critical Analysis from an Africentric Feminist Perspective - Mary V. Alfred (Adult Education Research Conference, 2000)
The Eurocentric worldview has dominated research and practice in adult higher education at the exclusion of other worldviews. Using the contours of the Africentric tradition, this paper examines the philosophical assumptions of andragogy and self-directed learning for their applicability to understanding and facilitating learning and knowledge construction among members of African descent.